Debt holder monitoring and implicit guarantees: Did the BRRD improve market discipline? - Jannic Alexander Cutura (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
This paper argues that the introduction of the Banking Recovery and Resolution Directive (BRRD) improved market discipline in the European bank market for unsecured debt. The different impact of the BRRD on bank bonds provides a quasi-natural experiment that allows to study the effect of the BRRD within banks using a difference-in-difference approach. Identification is based on the fact that (otherwise identical) bonds of a given bank maturing before 2016 are explicitly protected from BRRD bail-in. The empirical results are consistent with the hypothesis that debt holders actively monitor banks and that the BRRD diminished bail-out expectations. Bank bonds subject to BRRD bail-in carry a 10 basis points bail-in premium in terms of the yield spread. While there is some evidence that the bail-in premium is more pronounced for non-GSIB banks and banks domiciled in peripheral European countries, weak capitalization is the main driver.
Keywords: G18; G21; H81; 330